Karunia Roh menurut 1 Korintus 12:8-11 dan Penerapannya pada Ibadah - Yopi Tolego; Herman Liud (STT Bala Keselamatan Palu, 2022)
Abstract: This paper specifically discusses the gifts of the spirit in 1 Corinthians 12:8-11 and their application in worship. The methods used in writing this topic are qualitative methods with a literary study approach and an exposition approach to biblical texts. The result of this description in Greek uses the word: (didotai) which means to give, handing out, entrusting, giving back, putting, making and lifting. So the understanding of the